1990
DOI: 10.1073/pnas.87.10.3929
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxy-16-ene-23-yne-vitamin D3 prolongs survival time of leukemic mice.

Abstract: The 1,25-dihydroxy-16-ene-23-yne-vitamin D3 [1,25(OH)2-16-ene-23-yne-D3] is a vitamin D analog that is very potent in inhibiting proliferation and inducing differentiation of myeloid leukemic cells in vitro. Also, 1,25(0H)2-16-ene-23-yne-D3 is 300 times less active in mediating intestinal calcium absorption and bone calcium mobilization as compared to 1,25-dihydroxyvitamin D3 [1,25(OH)2D31, the physiologically active metabolite. Furthermore, 1,25(OH)2-16-ene-23-yne-D3 is 10-25 times less potent than 1,25(OH)2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(64 citation statements)
references
References 8 publications
2
62
0
Order By: Relevance
“…in 100 ll PBS, 3 times a week (Sunday, Tuesday and Thursday), according to the published protocol. 15,43,48 Cell inoculation and tumorigenicity assay Following acclimatization, mice were inoculated i.p. with 1 3 10 5 WEHI-3B D 2 cells in 100 ll sterile PBS 15 and randomly assigned to control and treatment groups (10 animals per group).…”
Section: Administration Of Vitamin D Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…in 100 ll PBS, 3 times a week (Sunday, Tuesday and Thursday), according to the published protocol. 15,43,48 Cell inoculation and tumorigenicity assay Following acclimatization, mice were inoculated i.p. with 1 3 10 5 WEHI-3B D 2 cells in 100 ll sterile PBS 15 and randomly assigned to control and treatment groups (10 animals per group).…”
Section: Administration Of Vitamin D Derivativesmentioning
confidence: 99%
“…15,43,48 Cell inoculation and tumorigenicity assay Following acclimatization, mice were inoculated i.p. with 1 3 10 5 WEHI-3B D 2 cells in 100 ll sterile PBS 15 and randomly assigned to control and treatment groups (10 animals per group). Twenty-four hours later, the mice were started on vehicle, Ro25-4020, rosemary extract or combination treatment.…”
Section: Administration Of Vitamin D Derivativesmentioning
confidence: 99%
“…5 Structural modifications of the side-chain itself also interfere with the C-24 hydroxylation-initiated cascade of degradation and modify biological activities. [6][7][8] These include C-23-yne or C-23(E,Z)-ene modifications and 26,27-hexafluorination. To reduce the inactivating C-3 epimerization, the A-ring can be modified as the 19-nor variant, 9 or by changing the geometry of the 5E double bond; 10 as a result, biological activities are enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] In vivo, the survival of mice challenged with syngeneic leukemic cells is enhanced by treatment with 1,25D 3 . 6, 7 Koeffler's group, 8 and later Kelsey et al, 9 reported that oral administration of 1,25D 3 to patients with myelodysplasia produced a partial but sustained hematological response, in terms of increases in neutrophil and platelet counts, in approximately half of the treated patients. However, hypercalcemia occurred in some patients before concentrations necessary for antileukemic activity could be achieved.…”
Section: Introductionmentioning
confidence: 99%